HISTAMIN DAN IDENTIFIKASI BAKTERI PEMBENTUK HISTAMIN PADA TUNA MATA BESAR (Thunnus obesus) - Stevy Imelda Murniati Wodi; Wini Trilaksani; Mala Nurilmala (Fakultas Perikanan dan Ilmu Kelautan, 2018)
Big eyes tuna (Thunnus obesus) is a species that potentially valuable as a source of protein and commercial aspect. In the perspective of quality and safety, inappropriate care during catching and processing leading to microorganism contamination and can cause health problems when the meat is consumed. Histamine content, total Histamine Forming Bacteria (HFB), and Total Plate Count (TPC) are the indicator in food safety and quality standard for tuna’s products. This research aims to measured histamine content, total HFB, TPC score and to identify the histamineforming bacteria in big eyes tuna observed during chilling temperature for nine days. There are three stages, sample preparation, storage, chemical and microbiology analysis. The During the observation period, histamine content, total HFB dan TPC score are increased in all part of the sample. Highest TPC sore is observed at day 9 which is 5,4 x 105 CFU/g in belly part, 5,1 x 105 CFU/g in dorsal part and 1,0 x 104 CFU/g in tail part respectively. For total HFB, 2,7 x 105 CFU/g in belly part, 1,4 x 105 CFU/g in dorsal part and 2,3 x 103 SFU/g in tail part respectively. For histamine content, all parts experienced increasing histamine measured 59,73 ppm, 131,10 ppm, and 96,04 ppm respectively. In this research, Bacillus subtilis is identified 99% as histamine forming bacteria in big eyes tuna.